2019
DOI: 10.1101/795740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Default mode network anatomy and function is linked to pediatric concussion recovery

Abstract: Objective:To determine whether anatomical and functional brain features relate to key persistent post-concussion symptoms (PPCS) in children recovering from mild traumatic brain injuries (mTBI), and whether such brain indices can predict individual recovery from PPCS.Methods: 110 children with mixed recovery following mTBI were seen at the concussion clinic at Neurology department Alberta Children's Hospital. The primary outcome was the Post-Concussion Symptom Inventory (PCSI, parent proxy). Sleep disturbance … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…We demonstrate that intra-network connectivity within the DMN–but not the SMN, SA, or FPN–is associated with accelerometer-measured LPA, MPA, and VPA within the first month of injury in pediatric concussion. Adding to the literature demonstrating associations between DMN impairment and concussion symptoms, depression, anxiety, and sleep-impairment 15,16 , we show that intra-network connectivity within DMN may be implicated with habitual physical activity within the first month of injury in children.…”
Section: Discussionsupporting
confidence: 55%
“…We demonstrate that intra-network connectivity within the DMN–but not the SMN, SA, or FPN–is associated with accelerometer-measured LPA, MPA, and VPA within the first month of injury in pediatric concussion. Adding to the literature demonstrating associations between DMN impairment and concussion symptoms, depression, anxiety, and sleep-impairment 15,16 , we show that intra-network connectivity within DMN may be implicated with habitual physical activity within the first month of injury in children.…”
Section: Discussionsupporting
confidence: 55%
“…Of the 8 articles, 2 studies 43,69 had participants undergo carbon dioxide stress testing using resting-state blood oxygenation level dependent to assess cerebrovascular responsiveness in youth with PPCS. In the first study, 70 patient-specific differences in PPCS individuals were observed in all participants. Voxel-by-voxel comparison of blood oxygenation level dependent cerebrovascular responsiveness for typically developing controls and PPCS patients showed a significantly greater response in 0.15% of the PPCS group, and significantly less responsiveness in 5.4% of the PPCS group.…”
Section: Functional Mrimentioning
confidence: 91%
“…In the second carbon dioxide stress-response study, 43 4 of 6 participants with PPCS demonstrated abnormal alterations in cerebrovascular responsiveness, using second-level analysis comparing youth with PPCS to typically developing control cerebrovascular responsiveness longitudinally. 43 A handful of studies assessed functional connectivity 46,60,67,[70][71][72] with mixed, but mainly significant, findings. In a study by Iyer and colleagues, 70 regional homogeneity (intraregional connectivity) and functional connectivity (interregional connectivity) in the posterior cingulate cortex was negatively correlated with sleep disturbances in individuals with PPCS compared to individuals with recovered concussion.…”
Section: Functional Mrimentioning
confidence: 99%
“…At one-month post-injury (the expected time of recovery 1 ), results of rs-fMRI studies are mixed 13,14,16-18 . With respect to studies of children diagnosed with PCS, one study found that within-network functional connectivity across seven validated brain networks did not differ between children with PCS (n=110) vs. healthy peers (n=20), although select PCS symptoms, sleep impairment, and poorer cognition were associated with connectivity in the concussed cohort 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies involved male only cohorts 14,16,21 , whereas others had less than 25% female representation in their samples 13,17 ; in some cases, data on sex were not reported 18,22 . Only a few studies had samples that approached balance (40-45% female) with respect to sex distribution 15,19,20,23 , though these studies did not stratify their results by sex, instead providing group-level data comparing mixed-sex cohorts of children with concussion to their healthy peers. The most direct data on sex-specific rs-fMRI differences come from a recent study involving adults with PCS 24 .…”
Section: Introductionmentioning
confidence: 99%